PENGEMBANGAN MATERIAL KONSTRUKSI RAMAH LINGKUNGAN MELALUI SUBSTITUSI PARSIAL SEMEN DAN PASIR DENGAN ABU SEKAM PADI DAN FLY ASH : PENGEMBANGAN MATERIAL KONSTRUKSI RAMAH LINGKUNGAN MELALUI SUBSTITUSI PARSIAL SEMEN DAN PASIR DENGAN ABU SEKAM PADI DAN FLY ASH - Irene Vista Simanjuntak; Sudarno P Tampubolon (UKI Press, 2025)
This study aims to develop an environmentally friendly construction material by partially substituting cement and sand with rice husk ash (RHA) and fly ash in pervious concrete. The combination of these two pozzolanic materials is expected to enhance the porosity of the concrete without causing a significant reduction in compressive strength, thereby maintaining its functionality while supporting rainwater conservation in urban areas. The experimental program consisted of a control concrete (without additives) and three modified mixes containing 10%, 15%, and 20% of combined pozzolanic materials (RHA and fly ash) as a partial replacement of the total binder, with a water–cement ratio (w/c) of 0.5 and up to 80% reduction in sand content. The results indicate that increasing the pozzolanic content proportionally increases the porosity and water absorption, from 5.9% in the control mix to 9.8% in the highest variation. Despite the higher porosity, the compressive strength remained within the range of 22–27 MPa, which satisfies the requirements for non-structural concrete. This demonstrates that RHA and fly ash can effectively replace a substantial portion of cement without significantly compromising performance. The pozzolanic reaction between active silica and Ca(OH)₂ generated secondary C–S–H gel formation, which strengthened the microstructure surrounding the pores. Overall, the incorporation of RHA and fly ash in pervious concrete produces a material with a balanced combination of strength, porosity, and environmental sustainability, offering great potential for application in sustainable drainage systems, permeable pavements, and urban green infrastructure. Keywords: Green Concrete; Rice Husk Ash; Fly Ash; Porosity; Compressive Strength; Pozzolanic Reaction; Sustainable Infrastructure.